Profil Ekosistem Terumbu Karang di Intertidal Pantai Balekambang, Kabupaten Malang, Jawa Timur - Alwan Alauddin Syah (LPPM Universitas Terbuka, 2023)
Concerns and vulnerabilities from the impact of rapid infrastructure growth in the Balekambang Beach area, Malang Regency can trigger damage to the existing coral reef ecosystem, especially in the intertidal zone. This is possible because it is not followed by awareness and understanding wisely by the surrounding community towards environmental conservation. The study aimed to determine the status of coral reefs, identify living corals, and measure the value of coral species diversity in the intertidal zone of Balekambang Beach, Malang Regency, East Java. The research used survey method with the help of Underwater Photo Transect (UPT) tool, the data was processed with Coral Point Count with Excel Extension (CPCe) software. The results showed that the percentage of coral cover varied in the range of 9.13%-21.53%, so it was included in the damaged category with poor sub-category. Identification of coral species at station 1 (BLCK01) was Favites spp., Gonioastrea spp., and Galaxea sp., at station 2 (BLCK02) found Favites spp., Gonioastrea spp., Platygyra sp.. Pocillopora spesicosa, and Porites sp. At station 3 (BLCK03), coral species Favites spp., Gonioastrea spp., Platygyra sp., Acropora spp., Pocillopra spesicosa, and Porites sp. The value of coral species diversity on this beach is included in the low category, namely 1.71-1.97.